Abortion Rights and European Constitutional Space: The Narrow Horizons of the Polish Legal System (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The purpose of this article is to provide a brief review of the social, political, normative, and jurisprudential developments that have led to the Polish legal system being one of the most restrictive on the subject of abortion rights in the European context. By critically analyzing these historical developments, we can determine whether we should accept a state of “global legal indeterminism” regarding voluntary interruption of pregnancy or if there are forces that can push national disciplines toward “minimum” standards shared on the European horizon and respect for a supra- and international concept of the rule of law.
Keywords: Abortion rights; Poland; Rule of Law; European multilevel architecture; European constitutional space